Development of category-based scoring support vector regression (CBS-SVR) for drought prediction. Issue 1 (17th January 2022) - Bazrkar, Mohammad Hadi; Chu, Xuefeng
Abstract: Using the existing measures for training numerical (non-categorical) prediction models can cause misclassification of droughts. Thus, developing a drought category-based measure is critical. Moreover, the existing fixed drought category thresholds need to be improved. The objective of this research is to develop a category-based scoring support vector regression (CBS-SVR) model based on an improved drought categorization method to overcome misclassification in drought prediction. To derive variable threshold levels for drought categorization, K -means (KM) and Gaussian mixture (GM) clustering are compared with the traditional drought categorization. For drought prediction, CBS-SVR is performed by using the best categorization method. The new drought model was applied to the Red River of the North Basin (RRB) in the USA. In the model training and testing, precipitation, temperature, and actual evapotranspiration were selected as the predictors, and the target variables consisted of multivariate drought indices, as well as bivariate and univariate standardized drought indices. Results indicated that the drought categorization method, variable threshold levels, and the type of drought index were the major factors that influenced the accuracy of drought prediction. The CBS-SVR outperformed the support vector classification and traditional SVR by avoiding overfitting and miscategorization in drought prediction. HIGHLIGHTS: Developed a category-based scoring support vector regression (CBS-SVR) method for drought prediction. Improved drought prediction by avoiding overfitting and miscategorization. The CBS-SVR outperformed the traditional SVR. The new method outperformed the support vector classification.